2021
DOI: 10.3390/insects12121116
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Traces of the Fruit Fly Anastrepha obliqua Associated with Its Polyphagous Nature

Abstract: Anastrepha obliqua (Macquart) (Diptera: Tephritidae) is an important pest in the neotropical region. It is considered a polyphagous insect, meaning it infests plants of different taxonomic families and readily colonizes new host plants. The change to new hosts can lead to diversification and the formation of host races. Previous studies investigating the effect of host plants on population structure and selection in Anastrepha obliqua have focused on the use of data from the mitochondrial DNA sequence and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…In both studies, the main differences were found in flies infesting carambola, which could be related to the chemical composition of these fruits and their recent introduction to the American continent (Velasco-Cuervo et al, 2021). Aguirre-Ramirez et al (2021) found similar results at the genomic level. Populations of A. obliqua infesting carambola have a greater genomic difference [based on restriction-site associated DNA sequencing (RAD-seq; Box 2] compared to populations infesting red mombin and mango.…”
Section: Qtls (Quantitative Trait Loci)supporting
confidence: 66%
See 2 more Smart Citations
“…In both studies, the main differences were found in flies infesting carambola, which could be related to the chemical composition of these fruits and their recent introduction to the American continent (Velasco-Cuervo et al, 2021). Aguirre-Ramirez et al (2021) found similar results at the genomic level. Populations of A. obliqua infesting carambola have a greater genomic difference [based on restriction-site associated DNA sequencing (RAD-seq; Box 2] compared to populations infesting red mombin and mango.…”
Section: Qtls (Quantitative Trait Loci)supporting
confidence: 66%
“…Populations of A. obliqua infesting carambola have a greater genomic difference [based on restriction‐site associated DNA sequencing (RAD‐seq; Box 2] compared to populations infesting red mombin and mango. Additionally, 54 single nucleotide polymorphisms (SNPs) were found to be associated with host plant use, some of which in protein families that could be annotated in pathways related to nutrition (Aguirre‐Ramirez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Rhagoletis cerasi (L.), the dynamics of Wolbachia infection can vary depending on the host plant, as in the process of ecological specialization, the vertical transmission of these bacteria is affected, as well as their gene flow. According to Aguirre‐Ramirez et al (2021), the populations of A. obliqua in southwestern Colombia could be in an incipient stage of specialization; therefore, we suggest that another factor responsible for the observed differences between metabarcoding and WMS is the possible divergence between populations of A. obliqua depending on the host plant.…”
Section: Discussionmentioning
confidence: 47%
“…Where each management unit could be colonized by sterile specimens derived from the same unit. This would also require developing strains compatible with each local population, by utilizing genomics differentiation in A. ludens populations and associations with different host plants and predicting the geographic and environmental ranges and relative abundances of invasive species using ecological niche modeling to give policies on a scientific basis (Santos et al, 2020;Aguirre-Ramirez et al, 2021;Gutierrez et al, 2021).…”
Section: Implications Of Genetic Diversity For Sterile Insect Techniq...mentioning
confidence: 99%